Artificial Intelligent in Congkak Game - Osman, Adnan (Universiti Teknologi Petronas, 2003)
Computer games provide a challenge for mankind. A way to demonstrate the mastery over the concept of intelligence. It is through a continual need to improve the artificial intelligence in computer games that man also finds a way to examine the creativity. Developments in the artificial intelligence of computer games have shown remarkable improvement as new genres of games have been created with new advances in the technology. Newer more complex and adaptable games demonstrate an increased understanding of intelligence and furnish entertaining benchmarks of our own ability. Congkak is a traditional game that is unique and famous in the early days. The game has certain properties that make ideal subjects for the research of AI technologies. It has a structured rules and tactics which are appropriate to generate the search space and liberated the research from the uncertainty and complexities inherent in less structured problems. With the science that is concerned with the automation ofintelligent behavior, though, this game has some advantages that hopefolly can introduce artificial intelligent system. For traditional game such as congkak, there is actually lack ofunderstanding the AI concept or methods used in the game. To be specific there is also lack oftraditional game in computer gaming market. The used of heuristic techniques is required for determining what alternatives to explore in the problem space. Heuristic technique is a major area ofAI research and it is useful for checking the best way to win or to protect from losing. Most ofushave some experience with this game and it is possible to devise and test the effectiveness of our own heuristics. For this reasons, congkak will provide a rich domain for the study of heuristic search. The study will also include research on interface development and performance wise. Basically, the intention of this study is to create a general and basic concept of an artificial intelligent technique that can be applied in traditional Malaysian games